Sistem Rekomendasi Alat Kesehatan PT. Romora Jaya Menggunakan Collaborative Filtering - Dicky Dwi Kurniawan; Muji Sukur (STEKOM PRESS, 2023)
The many types of medical devices available at PT. Romora Jaya Pratama makes customers confused in determining which medical device to buy. One of the solutions is to use a recommendation system that can help customers get the medical devices they want with collaborative filtering. This study aims to create a product recommendation system that can provide medical device product recommendations at PT. Romora Jaya Pratama with a collaborative filtering method based on a numerical rating, namely rating 1 which indicates the customer only sees the product and rating 2 indicates the customer buys the product. Collaborative filtering recommendations on PT. Romora Jaya Pratama can provide 3 product recommendations and best seller recommendations based on the most sales data in the current month and year as many as 3 products.